Inside channel - Hobbs, Tracey; Gregory, Sarah; Chiles, Andrian; BBC Learning (Australia : BBC Learning, 2003)
Overviewing the problem facing by Chanel, which is one of the world's most exclusive and expensive luxury brands. They need to attract younger clients and compete with the other luxury goods industries
Executive producer, Andrew McKerlie ; reporter, Andrian Chiles, series editor, Clive Edward
Keywords: Luxuries